Assessment on the weight of rabbits for meat fed on different ensilage types - Villa-Ramírez, Rigoberto; Hurtado-Villegas, Jaime (Universidad Pedagógica y Tecnológica de Colombia, 2016)
At the Quindio’s University experimental farm ”Benga|a", located in the municipality of Filandia, Quindio, the weight increase in rabbits for meat that were fed on different fodder was evaluated. The four treatments corresponded to the following ensilagesz imperial grass (Axonopus scoparius), imperial grass mixed with meadow buttercup (Tithonia diversifolia (Hemsl.), imperial grass mixed with ramie (Boehmeria nivea), and imperial grass mixed with morus/mulberry (/\/Iorus alba). The evaluation was applied on four probing groups consisting of five rabbits each. The group fed on imperial grass and meadow buttercup gained the highest increase of weight (2389 g in average), whereas the group fed on simply fresh fodder gained a lower mean weight 0f 2021 g. The food sources that better met the nutritional parameters of the rabbits were the following ensilages in due order: meadow buttercup, morus/mulberry, and ramie.